Modeling racial disparities in physical health via close relationship functioning: A life course approach. (May 2018) - Doyle, David Matthew; Factor-Litvak, Pam; Link, Bruce G.
Abstract: Objective: The aim of the present study was to test a life course model in which racial disparities in physical health between Caucasian and African Americans are driven by disparities in close relationship functioning. This model also examined relative evidence for intergenerational transmission of relationship functioning and ongoing exposure to prejudice and discrimination as two pathways that might shape adult relationship functioning. Method: A sample of 523 Caucasian and African American men and women were prospectively tracked from a birth cohort initiated in the 1960s. Reports of parental relationship functioning were obtained from participants and their mothers in adolescence. In midlife, participants completed measures of perceived discrimination (lifetime and everyday discrimination), close relationship functioning (relationship strain and support) and physical health (self-rated health, resting heart rate and systolic blood pressure). Results: As hypothesized, close relationship functioning was a strong predictor of physical health in adulthood. Furthermore, we observed that perceived discrimination over the life course was linked to impaired relationship functioning. Evidence for intergenerational transmission of relationship functioning was more equivocal. Conclusion: Racial disparities in physical health may be maintained via social factors throughout the life course. Although such factors have sometimes been considered outside the purview of the medical field, it is vital that researchers and clinicians begin to more fully address the implications of social forces in order to remediate racial health disparities. Highlights: Tests whether social factors influence racial health disparities. Utilizes a life course approach with proximal and distal factors. Close relationships shape racial disparities in physical health. Perceived discrimination mediates these associations. Little evidence for intergenerational transmission of relationship functioning.